The Impact of Audience Response System in Changing Students' Attitudes Towards Lectures During Training Courses; A Before‐After Study - Farzad Zareie; Rahim Baghaei; Naser Sheykhi; Davood Rasouli (Health Science Reports)
ABSTRACT Background and Aims The primary teaching approach known as “traditional lecture” has drawbacks, including being dull and reducing student participation, which has made students feel negatively about it. It seems that by implementing certain changes, active learning techniques like the “Audience Response System” could alter students' perceptions of lectures. The purpose of this study is to find out how employing “ARS” throughout a course has affected nursing students' perceptions of traditional lectures. Methods In present research, 44 nursing students participated in quasi‐experimental study (Pretest‐Posttest Design). A 5‐item, 5‐point Likert questionnaire and a pre‐test question regarding the degree of participation during lecture were used to gauge the students' attitudes towards lectures. Following that, a six‐session pharmacology course including “Lectures + ARS” was held. Following the completion of the course, the original questionnaire, a posttest question regarding attitudes, and four 3‐point Likert items regarding students' opinions regarding the use of ARS going forward were used to assess changes in the students' attitudes towards lectures. SPSS Ver. 26 was used for the data analysis. p < 0.05 was taken into consideration as the significance threshold. Results In comparison to before the course, the students' attitudes towards lectures had changed in a positive and significant way, specifically in items such as learning quality improvement, decreasing boredom, increasing participation and class activity. However, in the domain of “decreasing the use of lecture,” the ARS had failed to change the students' attitudes. 79.6% of students stated that the ARS had changed their attitudes towards lectures. More than 90% of students agreed with continued use of ARS in the future. Conclusion Lecturing could transform from a passive position to an active position by implementing ARS. Lecture + ARS could lead to improvement in students' class participation and activity, both of which are essential factors of an optimal education.